From head to toe [Od hlavy po päty anglicky] - Carle, Eric, 1929-2021 (Hamish Hamilton : Puffin, 1999)
A lively interactive introduction to basic body parts and movements from the creator of The Very Hungry Caterpillar.Gorillas, elephants, camels and other animals invite young readers to clap, stomp, wriggle and bend like they do!